Spectrophotometric Determination of Nickel with 3-Hydroxy-3-n-propyl-1-p-carboxyphenyltriazene - S. Shekhawat, Rajendra; S. Shekhawat, Rakesh; Singh, Raveendra; Chauhan, R.S.; Goswami, A.K.; Purohit, D.N. (Asian Journal of Chemistry, 2010)
The reagent 3-hydroxy-3-n-propyl-1-p-carboxyphenyltriazene has been used for spectrophotometric determination of Ni(II). It forms a light green ethanol soluble complex with Ni(II) in the ratio 1 : 2 (NiR2), with absorption maximum at 380 nm and optimum pH 6.8 to 8.0. The molar absorptivity and Sandell's sensitivity values are 7000 dm3 mol-1 cm-1 and 8.3 ng/cm2 respectively. Beer's law is obeyed over the concentration range of 0.3 ppm to 1.7 ppm of Ni(II). The stability constant has been worked out to be log β= 9.0. Standard deviation (10 determinations) for 4.69 ppm of Ni(II) has been found to be ±0.007 ppm. Interference studies have also been done.